Mathematical applications for the management, life, and social sciences - Harshbarger, Ronald J. (Houghton Mifflin, 2007)
Intended for a two-term applied calculus or finite mathematics and applied calculus course, Mathematical Applications, 8/e, presents concepts and skills in an approachable way for students of varying abilities and interests. The Eighth Edition retains the features that have made this text a popular choice, including applications covering diverse topics that are important to students in the management, life, and social sciences. This edition broadens the represented applications by adding a number of environmental science applications. The use of modeling has also been expanded, with modeling problems now clearly labeled in the examples